PERAN MOTIVASI KERJA MEMEDIASI PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN FAIRMONT SANUR BEACH HOTEL - Sari, Ni Putu Sinta Kumala; Sriathi, A.A Ayu (E-Jurnal Manajemen; Vol 8 No 8 (2019), 2019)
The purpose of this research was to examine the role of mediation work motivation on the effect on performance of employee career development. This research was conducted at the Fairmont Hotel Sanur Beach with samples as many as 72 people are determined by the method of proportionate stratified random sampling. The collection of data obtained from the results of the dissemination of the questionnaire by using as many as 13 indicators. As for the data analysis technique used in this study i.e. path analysis (path analysis) accompanied by sobel test. The results showed that the career development positive and significant effect on performance and motivation of the employees work. Motivation work positive and significant effect on performance as well as employees are able to mediate the influence of career development employee performance against. The results suggested that the better career development in the enterprise the higher the employee motivation, and higher employee motivation will be higher performance Fairmont Hotel Sanur Beach. Keywords: career development, work motivation, employee performance